Desarrollo de una aplicación web y móvil para automatizar los pedidos y reservaciones de comidas en la cafetería “Dulzura Mía” ubicada en el cantón Pujilí aplicando prácticas ágiles - Soria Suntasig, Jeferson Fabricio (2022)
This technological proposal deals with the development of a web and mobile application with the objective of automating the orders and reservations of the Cafeteria "Dulzura Mía" located in the canton of Pujilí, province of Cotopaxi. The problem that arose in the cafeteria was that it did not have the appropriate technology for the respective management of sales with home deliveries, resulting in economic losses and low market share. For the implementation and design of the application, the respective free software tools were used, such as: Java, Python, Django, Django Rest Framework, PostgreSQL Database Management System. The Mobile-D Methodology was used for the respective implementation of the mobile application, which allows fast results and is characterized by working with small groups. For the web application, the Scrum methodology was applied because it provides greater communication between the client and the development team, allowing for greater productivity and quality of the final product. With the implementation of the web and mobile application in the Cafeteria "Dulzura Mía" has benefited at the time of receiving orders from users which is done with great fluidity and efficiency, resulting in an innovative service for the customer.